ZEB1 enhances Warburg effect to facilitate tumorigenesis and metastasis of HCC by transcriptionally activating PFKM - Zhou, Yanming; Lin, Furong; Wan, Tao; Chen, Ai; Wang, Huihui; Jiang, Bin; Zhao, Wentao; Liao, Shan; Wang, Shijie; Li, Guannan; Xu, Zhenzhen; Wang, Jinyang; et al. (Theranostics, 2021)
Metabolic reprogramming, especially Warburg effect, is a key event in tumor initiation and progression. ZEB1 plays a vital role in metastasis of various cancers. We previously found that ZEB1 was excessively expressed in hepatocellular carcinoma (HCC) and its high expression was closely correlated with metastasis and recurrence of HCC. We want to know whether glycolytic enzymes are regulated by ZEB1 and contribute to carcinogenesis and metastasis of HCC. To explore whether ZEB1 could enhance glycolysis in HCC, we knocked down ZEB1 by short hairpin RNA (shRNA) in MHCC-97H and HCC-LM3 cells and performed glucose uptake, lactate production, ECAR and OCR assays. To investigate how ZEB1 enhances glycolysis, the protein levels of glycolytic enzymes were detected in the same cell lines using Western blot. The regulatory effect of ZEB1 on PFKM mRNA level was confirmed by RT-qPCR, luciferase report assay and ChIP assay. In order to assess the role of ZEB1-PFKM axis in cell proliferation, cell counting and CCK-8 assays were performed in MHCC-97H and HCC-LM3 cell lines knocked down for ZEB1 and further re-expressed for either ZEB1 or PFKM or not. To explored whether the ZEB1-PFKM axis also functions in HCC cell migration, invasion and metastasis, the same MHCC-97H and HCC-LM3 cell lines were performed for wound healing assays, transwell assays and colony formation assays, meanwhile, MHCC-97H cell lines were performed for orthotopic liver transplantation assays. Finally, the expression of ZEB1 and PFKM were examined in human liver cancer specimens and non-tumorous liver tissues using immunohistochemical and Western blot. We found that ZEB1 transcriptionally upregulates the expression of the muscle isoform of phosphofructokinase-1 (PFKM), a rate-limiting enzyme in glycolysis. Intriguingly, a non-classic ZEB1-binding sequence in the promoter region of PFKM was identified through which ZEB1 directly activates the transcription of PFKM. Silencing of ZEB1 in MHCC-97H and HCC-LM3 cell leads to impaired PFKM expression, glycolysis, proliferation and invasion, and such impairments are rescued by exogenous expression of PFKM. Importantly, HCC xenograft assays and studies from TCGA database demonstrate that ZEB1-PFKM axis is crucial for carcinogenesis and metastasis of HCC. Our study reveals a novel mechanism of ZEB1 in promoting HCC by activating the transcription of PFKM, establishing the direct link of ZEB1 to the promotion of glycolysis and Warburg effect and suggesting that inhibition of ZEB1 transcriptional activity toward PFKM may be a potential therapeutic strategy for HCC.